Review of Hajj Fund Management in Indonesia Between 2018 – 2023 - Ilhami, Muhammad Rifqi; Sattar, Abdul (UPT Jurnal & Publikasi Ilmiah SPs Universitas Ibn Khaldun Bogor, 2025)
The main purpose of this research is to describe how the financial management of Hajj in Indonesia (BPKH) in performing its duties from 2018 to 2023. In this way, it will be clear what and how BPKH manages Hajj funds, which amount to hundreds of trillions of rupiah. The author analyzes the financial statements of BPKH from 2018 to 2023.The BPIH adjustment pattern, Bipih, and the value of benefits are secondary data that we use as the main raw material to see the performance of BPKH in managing Hajj funds. Then, the financial statements will be calculated annually so that the difference in net profit generated by BPKH will be seen. This research uses a qualitative approach. Researchers used secondary data in the form of books on Hajj financial management and BPKH annual financial reports as well as articles from relevant research findings. The method used in this article is library research using the systematic literature review (SLR) technique. The results of this study indicate that BPKH in managing Hajj funds in Indonesia still faces challenges in reporting transparency, internal control effectiveness, and compliance. The imbalance between benefit value receipts and BPIH subsidies has the potential to pose a liquidity risk and unsustainability of Hajj finances.